El servicio de mesa para líquidos en el Garb al-Andalus: formas, técnicas y ornamentación - Gómez Martínez, Susana (2020)
At the International Congress on Medieval pottery in Western Mediterranean, held in Lisbon in 1987, Juan Zozaya and Manuel Retuerce presented “Variants and constants in Andalusian ceramics” in which they made a chrono-typological synthesis of tableware in al-Andalus..With this work we intend to follow the steps of our tutor, making a synthesis about the table service for liquids in the extreme Garb al-Andalus, the current Portuguese territory, analyzing forms and their evolution, manufacturing techniques and the ornamentation about one of tableware forms for liquids, the jar and jar/jug (jarra/jarrita in Spanish and bilha in Portuguese).